Perilaku Ibu dalam Memberikan Pendidikan Seks Usia Dini pada Anak Pra Sekolah (Studi Deskriptif Eksploratif di TK IT Bina Insani Kota Semarang) - Astri Aprilia (Jurnal Kesehatan Masyarakat (Undip), 2015)
Sex educationislearning, realizing, and providing information about sex. The information which is provided includes knowledgeaboutthe function ofthe reproductive organ sby applying morals, ethics, commitment, faithto prevent"abuse" of the reproductive organs. At the present time, many children experience the early maturing and there is a growing number of sexual abuse of children. The purpose of the research is to describe mother’s behaviour in giving sex education in early age for pre school children, including practices, knowledges, attitudes, subjective norms, behavioral believe, intentions and behavioral deviation in children. This kind of research isa qualitative descriptive exploratory approach. The subjects of the research were selected by purposive sampling of 7 people. The validityof the research  uses sources triangulation, methods and theories. The data were analyzed using content analysis. Theory ofPlanned Behavior is used in the framework of this analytical research. The variablesexamined in this studyarethe personal characteristics ofthe mother, mothers’ attitude toward the behavior, subjective norms, behavioral control of mothers’ intention and mothers’ practices in giving sex education in early age for pre school children.The result of the research shows that mothers’ knowledge related to sex education is still limited. Mothers have not understood about the restrictions that must be given for pre school children according to the existing theories. It is proved that mothers are still hesitate and not sure with what is delivered according to the norms and beliefs of each mother. Mothers’ attitude in giving sex education has been good, so does  the husband. But there are still mothers who do not understand the best way to answer the children’s questions. Mothers already have the intention in providing sex education for pre school children, it is proved from the mothers’ effort in finding the studies of Sex Education in early age. Mothers’ practices have been good, but the studies of the restriction that must be given to the children has not been known by mothers. The conclusion is that giving sex education in early age for pre school children is still not appropriate according to the limitation of children’s age because it is still considered taboo by mothers in providing the understanding to the children.